Study of muon-induced background in MMC detector arrays for the ECHo experiment - Göggelmann, Alexander; Jochum, Josef; Gastaldo, Loredana; Velte, Clemens; Mantegazzini, Federica (The European physical journal. C, Particles and fields, 2021)
For above ground particle physics experiments, cosmic muons are common source of background, not only for direct detector hits, but also for secondary radiation created in neighboring materials. The ECHo experiment has been designed for the determination of the effective electron neutrino mass by the analysis of the endpoint region of the $$^{163}\text {Ho}$$electron capture spectrum. The fraction of events occurring in the region of interest of 10 eV below the $$Q_{EC}$$value of about 2.8 keV is only of the order of $$10^{-9}$$. This means that the background in that region need to be studied, characterized and methods to suppress it need to be developed. We expect a major background contribution to be due to cosmic muons and radiation produced by muons traveling through material around the detectors. To determine the muon-related background in metallic magnetic calorimeters (MMCs) used in the ECHo experiment, we have performed an experiment in which a muon veto was installed around the cryostat used for the operation of the detectors. We analysed the acquired events to investigate the pulse shape of MMC events in coincidence with the muon veto and the rate of multiple coincidences among detector array pixels. With different methods used for identification of muon related events, we studied events generated by muons and secondary radiation depositing energy in the substrate close to the ECHo pixels. In addition, energy depositions of muons and secondary radiation in the detectors was studied via Monte Carlo simulation. At the present status of investigation, we conclude that muon related events will be a negligible background in the region of interest of the $$^{163}\text {Ho}$$spectrum.
Gesehen am 23.05.2022